"Can I do well in mathematics reasoning?" Comparing US and Finnish students' attitude and reasoning via TIMSS 2011. Issue 7 (17th November 2017) - Hwang, Jihyun; Runnalls, Cristina; Bhansali, Sneha; Navaandamba, Khajidsuren; Choi, Kyong Mi
ABSTRACT: This study investigated differences between the US and Finland in terms of how students' attitude is related to mathematical reasoning skills through the Trends in International Mathematics and Science Study (TIMSS) 2011. Attitude towards mathematics was observed via 3 TIMSS contextual variables: liking mathematics, valuing mathematics, and confidence in mathematics. Scores for mathematical reasoning were collected from the TIMSS 2011 database. We used hierarchical linear modelling to construct multilevel models with interactions of the attitude variables. Findings showed that confidence in mathematics had the strongest positive relationships with mathematical reasoning in both countries. Finnish students generally reported stronger positive relationships between confidence in mathematics and reasoning than US students. Strong relationships between confidence and reasoning remained visible when examining valuing and liking mathematics. Findings provide important implications regarding the complex interactions between attitude towards mathematics and reasoning, critical for mathematics educators and policymakers to consider in an increasingly competitive international environment.